Lower Paleolithic Shaped Stone Balls—What Is Next? Some Cultural–Cognitive Questions - Ella Assaf; Javier Baena Preysler; Emiliano Bruner (Quaternary, 2023)
Shaped stone balls (SSBs) were an integral part of human culture across the Old World for nearly 2 million years. They are one of the oldest implements made and used by humans. In this significant era, which was characterised by biological and cultural transformations, these round implements were a stable hallmark throughout the Lower Paleolithic period and beyond. However, while much research progress has been made in other stone tool categories, and despite the increased research efforts in recent years, attempts to define SSB function and typology have remained inconclusive, and broader cultural and cognitive aspects related to their production techniques, use and dispersal have yet to be explored in depth. What is the significance of their continuous presence and wide geographical distribution? What do these imply regarding the cognitive abilities of Oldowan and Acheulian humans? In this paper, we turn the spotlight on these enigmatic items. We address unresolved issues and explore the ergonomic and perceptual properties stimulated by the geometry of these items. We show that stone ball variability matches (modern) human hand palm variability. Moreover, when using SSBs in percussion activities, they are handled with the entire palm. Following, we discuss the role of SSBs in the context of socio-cultural processes. We suggest that SSBs reflect some of the earliest evidence in human history of a specific form that was conceptualised and recurrently acted upon.